Stella - Getchell, Robert; Goldwyn, Samuel; Erman, John.; Midler, Bette; Goodman, John.; Alvarado, Trini; Peldon, Ashley; Touchstone Pictures ([Burbank, Calif.] Touchstone Pictures and the Samuel Goldwyn Co., 1990)
Tough and independent Stella discovers that she is pregnant after a brief affair with a doctor. She raises her daughter Jenny alone in a loving relationship, until Stella realizes that there are advantages that only Jenny's wealthy father could provide.
VHS.
Based on the novel "Stella Dallas" by Olive Higgins Prouty.
Co-producer, Bonnie Bruckheimer-Martell ; executive producer David V. Picker.
Bette Midler, John Goodman, Trini Alvarado, Stephen Collins and Marsha Mason, Ashley Peldon.
Keywords: Drama